Peran Komunikasi Interpersonal dalam Membangun Identitas dan Budaya Organisasi - Indri Febrianti; Malika Ayumi; Azhari Panjaitan; Afwan Syahril Manurung (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Interpersonal communication plays a crucial role in building trust, collective identity, and a positive organizational culture. In organizations, trust serves as the primary foundation for creating a productive work environment, while collective identity and organizational culture shape internal direction and stability. This study aims to analyze the role of interpersonal communication in supporting these three elements. The research adopts a literature review method by examining various sources, including books, scholarly journals, and other relevant documents. The findings reveal that open, transparent, and effective interpersonal communication strengthens mutual trust, facilitates the formation of collective identity through social interactions, and fosters a harmonious organizational culture. Furthermore, interpersonal communication proves to be key in resolving conflicts constructively. This study highlights the importance of effective communication strategies to enhance interpersonal relationships within organizations and achieve shared goals.